PENGARUH PARTISIPASI PENGANGGARAN DAN KOMITMEN ORGANISASI PADA KINERJA MANAJERIAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Harlista Sukmantari, Dewa Ayu Made; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
This study describes the impact of budgetary participation and organizational commitment to managerial performance and job satisfaction as an intervening variable, a case study on the Regional Enterprise of Parking Denpasar city. This study aims to observe the impact of (1) budgetary participation to job satisfaction, (2) organizational commitment to job satisfaction, (3) budgetary participation to managerial performance, (4) organizational commitment to managerial performance, and (5) job satisfaction to performance managerial. Data obtained by survey method using questionnaire. Sample of 32 questionnaires were distributed to the chief executive and his staff were involved in the budgeting process. Once collected, the data is processed wear path analysis to measure the effect of direct and indirect budgetary participation, organizational commitment on managerial performance. Conclusion of the study showed a direct and indirect influence between budgetary participation to job satisfaction, organizational commitment to job satisfaction, budgetary participation to managerial performance, organizational commitment to managerial performance, and job satisfaction to managerial performance.
Keywords: Participation budget, organizational commitment, job satisfaction, managerial performance.